Cytomegalovirus in Haematological Tumours - Alonso-Álvarez, Sara; Colado, Enrique; Moro-García, Marco A.; Alonso-Arias, Rebeca (Frontiers in Immunology, 2021)
The exquisite coupling between herpesvirus and human beings is the result of millions of years of relationship, coexistence, adaptation and divergence. It is probably based on the ability to generate a latency that keeps viral activity at a very low level, thereby apparently minimising harm to its host. However, this evolutionary success disappears in immunosuppressed patients, especially in haematological patients. The relevance of infection and reactivation in haematological patients has been a matter of interest, although one fundamentally focused on reactivation in the post-allogeneic stem cell transplant (SCT) patient cohort. Newer transplant modalities have been progressively introduced in clinical settings, with successively more drugs being used to manipulate graft composition and functionality. In addition, new antiviral drugs are available to treat CMV infection. We review the immunological architecture that is key to a favourable outcome in this subset of patients. Less is known about the effects of herpesvirus in terms of mortality or disease progression in patients with other malignant haematological diseases who are treated with immuno-chemotherapy or new molecules, or in patients who receive autologous SCT. The absence of serious consequences in these groups has probably limited the motivation to deepen our knowledge of this aspect. However, the introduction of new therapeutic agents for haematological malignancies has led to a better understanding of how natural killer (NK) cells, CD4+ and CD8+ T lymphocytes, and B lymphocytes interact, and of the role of CMV infection in the context of recently introduced drugs such as Bruton tyrosine kinase (BTK) inhibitors, phosphoinosytol-3-kinase inhibitors, anti-BCL2 drugs, and even CAR-T cells. We analyse the immunological basis and recommendations regarding these scenarios.